Paddy supply chain: a case of paddy industry in Kelantan / Azmahani Yaacob @ Othman, Zulkorain Yusop and Syazwani A Malek @ Abdul - Yaacob @ Othman, Azmahani; Yusop, Zulkorain; A Malek @ Abdul, Syazwani (Faculty of Business and Management, Universiti Teknologi MARA, Shah Alam, Malaysia.., 2019)
The production of paddy and the supply of rice to the consumers should not be viewed as separate segments but as a series of linked segments within a supply chain model. It involved of both upstream and downstream linkages. Each linkage has different processes and activities that produce different value and form of products and services before it reaches to the final customer or consumer. The paddy supply chain in Kelantan starts with the paddy producers (farmers), to the rice millers, then to the traders who will hand it to the wholesale traders, and lastly to the final consumers. A strong linkage between actors in every stage of supply chain can guarantee a competitive production and efficient distribution of paddy and rice from farmers to the final consumers.